GOD's PRISONERS: PENAL CONFINEMENT AND THE CREATION OF PURGATORY - Skotnicki, Andrew (Modern theology, 2006)
This essay explores two events that occurred in the thirteenth century: the decree normalizing the prison as the fundamental disciplinary apparatus in the first universal system of law (canon law) and the formal recognition by the Catholic Church of the existence of Purgatory. It will be suggested that this simultaneity was far from coincidental. The penal colony known as Purgatory reflected in nearly exact detail the contours of the earthly prison. Implications for modern theology will then be discussed.